DEVELOPMENT AND OPTIMIZATION OF TAZAROTENE LOADED SOLID LIPID NANOPARTICLES FOR TOPICAL DELIVERY - RAJKUMAR ALAND,; GANESAN M,; RAJESWARA RAO P, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Psoriasis is an unswervingly recurring, inflammatory, autoimmune disorder of the skin, disturbing about 2–5% of the world population. The main objective for this investigation is to develop and optimize the solid lipid nanoparticles (SLN) formulation of tazarotene for effective drug delivery. Methods: Tazarotene SLNs were fabricated by hot homogenization followed by the ultrasonication using Taguchi’s orthogonal array with eight parameters that could affect the particle size and entrapment efficiency (EE). In view of the outcomes from the examinations of the responses acquired from Taguchi design, three diverse independent variables including sonication time (s), lipid to drug ratio (w/w), and surfactant concentration (%) were carefully chosen for further investigation utilizing central composite design. The lipid dynasan-116, surfactant poloxamer-188, and cosurfactant egg lecithin resulted in better percent drug loading and evaluated for particle size, drug EE, zeta potential, in vitro drug release, and stability. Results: The prepared nanoformulations were evaluated for different parameters and found to be in an acceptable range. In vitro drug release of optimized SLN formulation (F1) was found to be 98.12±1.52%, whereas pure drug release was 42.12 after 60 min, and the major mechanism of drug release follows zero-order kinetics release data for optimized formulation (F1) with non-Fickian (anomalous) with a strong correlation coefficient (R2=0.98598) of Korsmeyer-Peppas model. Transmission electron microscopy analysis has demonstrated the presence of individual nanoparticles in spherical shape, and the results were also compatible with particle size measurements. The drug content of tazarotene gel formulation was found to 98.96±0.021%, and the viscosity of gel formulation at 5 rpm was found to be 5.98×103±0.34×103 cp. The release rate (flux) of tazarotene across the membrane and expunged skin diverges pointedly, which specifies the barrier nature of skin. The flux value for SLN based gel formulation (193.454±4.324 μg/cm2/h) was found to be higher than that for marketed gel (116.345±2.238 μg/cm2/h). The higher flux and Kp values of SLN based gel suggest that it might be able to enter the skin easily as compared with marketed gel with an advantage of low interfacial tension of the emulsifier film that ensures an excellent contact to the skin. Conclusion: From the obtained results, the topically oriented SLN-based gel formulation of tazarotene could be useful in providing effective and site-specific psoriasis treatment.